Development of the Coordination Dimension of Relational Capabilities: Comparison between For- Profit and Non-profit Technology Transfer Partnerships - Alves, Fernanda Salvador; Segatto, Andréa Paula; Vieira Cruz Kumasaka, Júlia Mitsue; De-Carli, Eduardo; Domingues De Lima, Ana Karolina (International Journal of Supply Chain Management, 2022)
In order to ensure the success of a technology transfer partnership for-profit or non-profit, it is necessary to understand which relational capabilities (RC) to explore. This article analyses which factors can assist in the development of the coordination dimension of RC, in cooperation with the development of non-profit and profit-oriented technologies, highlighting their similarities and differences. The method used was multi-case qualitative research, studying two groups (group N and group P), each with 5 entities. The main differences highlighted is the increase of social credibility for the group N and the knowledge dissemination of the partners and the processes improvement for the group P. Within this research, it was possible to deepen the model of Alves (2015), regarding the inclusion of factors that can help the development of RC Management dimensions. Understanding capabilities development in each alliance is the implication of the study.